ADAPTASI ALAT UKUR DIFFERENTIATED PROCESS SCALE OF SELF-FORGIVENESS - Febiana, Reva; Malay, Mohammad Nursalim; Wahyuni, Citra (Jurnal Psikologi, 2024)
Self-forgiveness has been proven to greatly benefit an individual's mental health and help them live a better life. This study aims to adapt a measuring instrument using Rasch modeling to obtain a valid and quality measuring instrument. In addition, the Rasch model can also predict missing data, evaluate the similarity of answers, and identify the seriousness of respondents. In adapting the measuring instrument, 6 stages must be carried out. The research subjects were 214 participants selected using convenience sampling with the criteria of early adulthood aged 18-25 years. Overall, this adaptation can be said to be good in measuring the construct of self-forgiveness in the context of Indonesian culture based on testing the Rasch model. The results of the data analysis that have been carried out using the Rasch model are that for person reliability it gets a value of 0.83 while for item reliability it gets a value of 0.99. The average value of INFIT MNSQ and OUTFIT MNSQ in people is 0.98 and 1.00, and in items, it is also 0.98 and 1.00. A value approaching 1.00 is considered good. For INFIT ZSTD and OUTFIT ZSTD, the average values for individuals were -0.2 and -0.1, while for items they were -0.3 and 0.0, with the ideal value approaching 0.0. The results show that these values are classified as good. In addition to obtaining an accurate measuring instrument, this study is also useful in clinical practice so that it can be used to identify and overcome obstacles in the self-forgiveness process.